Application of Multivariate Statistics and Geostatistical Techniques toIdentify the Distribution Modes of the Co, Ni, As and Au-Ag ore in theBou Azzer-East Deposits (Central Anti-Atlas Morocco) - Muhammad Souiri (2020)
The polymetallic Co, Ni, Cu, As, Au, and Ag deposits of Bou Azzer East are located in the western part of the Bou Azzer inlier in the Central Anti Atlas, Morocco. Six stages of emplacement of the mineralization have been identified. Precious metals (native gold and electrum) are present in all stages of this deposit except the early nickeliferous stage. From the Statistical analysis of the Co, As, Ni, Au, and Ag contents of a set of 501 samples, shows that the Pearson correlation coefficient between As-Co elements (0.966) is the highest followed by that of the Au-Ag couple (0.506). Principal Component analysis (PCA) and hierarchical ascending classification (HAC) of the grades show, that Ni is associated with the pair (As-Co) and Cu is rather related to the pair (Au-Ag). The kriging maps show that the highest values of the Co, As and Ni appear in the contact of the serpentinite with other facies, as for those of Au and Ag, in addition to anomalous zones concordant with those of Co, Ni and As, they show anomalies at the extreme South and North of the study area. The development of the anomalous Au and Ag zones is mainly along the N40-50°E and N145°E directions.